IMPLEMENTATION OF GOOD GOVERNANCE, BUDGET PARTICIPATION, AND ORGANIZATIONAL COMMITMENT IN EFFORTS TO REDUCE BUDGET GAP - I Gusti Ayu Made Asri Dwija Putri; Ni Gusti Putu Wirawati; Komang Ayusta Devi Savitri; Ni Made Dwi Okayanti (Ekuitas: Jurnal Ekonomi dan Keuangan)
This study aims to analyze and obtain empirical evidence that budget participation affects budgetary slack. Another objective is to prove that good governance and organizational commitment can weaken the effect of budget participation on budgetary slack. This study is quantitative. The population of the study was all Regional Apparatus Organizations (OPD) in Gianyar Regency. The research sample was 28 OPDs. Data were collected by distributing questionnaires directly to each OPD. The research variables include budget participation, good governance, organizational commitment and budgetary slack. The measurement of variables uses a Likert scale. The analysis technique uses moderation regression analysis. The results of the study prove that Budget participation has a positive effect on budgetary slack. Therefore, the higher the level of budget participation, the greater the possibility of budgetary slack occurring. Good governance weakens or reduces the effect of budget participation on budgetary slack. At the same time, organizational commitment has no effect or cannot moderate the relationship between budget participation and budgetary slack.